Eco-literasi PENINGKATAN ECOLITERACY SISWA SEKOLAH DASAR MELALUI PROGRAM PENGABDIAN MASYARAKAT : - - I Made, Putrawan (LPPM IAIN Sultan Amai Gorontalo, 2025)
The development process around the world is faced with a dilemma, namely whether development keep going continued, consider the impact it causes, namely damaging environment. One proof is and more it's hot earth's temperature as a result of clearing forests for the sake of generating development various crisis environments is one of them is global warming. This is thought to be caused by the